101 Children and young people's perspective on decision-making and their experiences around selective dorsal rhizotomy. (15th December 2021) - Chugh, Deepti; Waite, Gill; Harniess, Philip; Oulton, Kate; Wray, Jo; Cawker, Stephanie
Abstract : Background: Selective dorsal rhizotomy (SDR) is a neurosurgical procedure used to permanently reduce spasticity in the lower limbs of children with bilateral spastic cerebral palsy (CP). Little information exists on the extent to which children and young people (CYP) participate in decision-making around SDR. This study explored the experiences, expectations and CYP involvement in the decision-making for SDR surgery, post-operative physiotherapy treatment and outcomes. Method: A qualitative study using 1:1 interviews utilising creative methods was conducted. Five CYP (2 girls and 3 boys) participated, and interviews lasted between 45 minutes to 2 hours. Data were analysed using thematic analysis. Results: CYP are heavily reliant on their parents to make decisions and inform them of the process. Their focus remains on the social issues (school, friends, competing demands), the psychological and physiological challenges of CP that they experience in their daily lives. The CYP involvement in the SDR process changes from being a passive onlooker during the decision-making process to becoming an active participant after the surgery. Individual characteristics and attributes of CYP have an impact on how they cope with the rehabilitation burden, adjust to their changing levels of function and participation. Gaps around the lack of availability of child-friendly resources, knowledge and psychological preparedness for surgery and burden of rehabilitation following SDR have been identified. Conclusion: Although SDR offered CYP the benefit of 'freedom to choose' and improved participation in daily life, further consideration is required to meet their psychosocial needs, particularly in preparing for SDR and adjusting afterwards. Providing age-appropriate information, resources to help parents and psychological support for CYP are integral to facilitate them through the decision-making and post-operative intensive rehabilitation.